Peningkatan Akurasi Pada Sistem Monitoring Posisi Kapal Menggunakan Metode Kalman Filter - Herianto Herianto; Fajri Profesio Putra; Muhammad Asep Subandri (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
This research produces a monitoring system to determine the position of the ship using the Kalman Filter method in web-based system development using the waterfall development method. This system allows users to view the position and coordinates of the ship in real-time. By applying the Kalman Filter method, uncertainty and noise in measuring the position of the ship can be reduced, thereby increasing the accuracy in determining the actual position of the ship. The system development process is carried out using the waterfall method which consists of requirements analysis, design, implementation, testing, and maintenance. The developed web-based system provides more accurate and reliable information to users, with the ability to view the position and coordinates of the ship in real time. This research contributes to the development of a more effective ship position monitoring system that can be used in various purposes such as navigation, surveillance, and ship monitoring.